PEMBELAJARAN DALAM MEMANFAATKAN POTENSI OTAK - Henni Sukmawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2022)
One form of learning is information processing which is analogous to our mind or brain which acts like a computer, where there is input and information storage in it. what our brain does is how to get back the information material in the form of images or writing. Learning is a thinking process learning thinking emphasizes the process of seeking and finding knowledge through interactions between individuals and the environment. In learning to think is that knowledge does not come from outside, but is formed by the individual himself in his cognitive structure. Learning to think is the maximum utilization and use of the brain, the human brain consists of two parts, namely the right brain and the left brain. Each hemisphere of the brain specializes in certain abilities. Both hemispheres of the brain need to be developed optimally and balanced, learning that only tends to use the left brain by forcing children to think logically and rationally will make children in a dry and empty position learning to think logically and rationally needs to be supported by the movement of the right brain. Therefore, in the standard of the educational process, learning is to use both hemispheres of the brain in a balanced way.